Nesfatin-1 increases intracellular calcium concentration by protein kinase C activation in cultured rat dorsal root ganglion neurons - Ozcan, Mete; Gok, Zeynep Betul; Kacar, Emine; Serhatlioglu, Ihsan; Kelestimur, Haluk (Elsevier Ireland Ltd, 2016)
Nesfatin-1 is a recently identified anorexigenic hypothalamic polypeptide derived from the posttranslational processing of nucleobindin 2 (NUCB2). Several studies have indicated that this neuropeptide may be participated in somatosensory and visceral transmission including pain signals in addition to energy metabolism. The aim of this study was to explore the possible role of nesfatin-1 in the transmission of peripheral neural signals by investigating the effects of nesfatin-1 on intracellular free calcium levels ([Ca2+](i)) in cultured neonatal rat dorsal root ganglion (DRG) neurons. The effects of nesfatin-1 on [Ca2+](i) in DRG neurons were investigated by using an in vitro calcium imaging system. DRG neurons were grown in primary culture following enzymatic and mechanical dissociation of ganglia from 1-or 2-day-old neonatal Wistar rats. Using the fura-2-based calcium imaging technique, the effects of nesfatin-1 on [Ca2+](i) and role of the protein kinase C (PKC)-mediated pathway in nesfatin-1 effect were assessed. Nesfatin-1 elevated [Ca2+](i) in cultured DRG neurons. The response was prevented by pretreating the cells with pertussis toxin. The protein kinase C inhibitor chelerythrine chloride suppressed nesfatin-1-induced rise in [Ca2+](i). The result shows that nesfatin-1 interacts with a G protein-coupled receptor, leading to an increase of [Ca2+](i) which is linked to protein kinase C activation in cultured rat DRG neurons. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Nesfatin; Sensory neurons; Calcium signaling; Protein kinase-C; G protein; Pain